Ectopic pregnancy and unsupervised abortion pills: the hidden truth - Singh, Neha; Pathania, Kushla; Negi, Kalpna; Rathod, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Aim of the study was the indiscriminate use of self-consumption of abortion pills and its association with complication like ectopic pregnancy reporting to a tertiary care center. Methods: The study was a prospective observational study conducted in the department of obstetrics and gynecology, Kamla Nehru State hospital for mother and child, Indira Gandhi medical college Shimla w.e.f. 1st July 2018 to 30th June 2019. A total of 27 women reported to the hospital who were diagnosed of having ectopic pregnancy after intake of abortion pills. Results: A total of 27 cases presented to the hospital who were diagnosed to have ectopic pregnancy. Maximum 18 (67%) cases were in 21-30 years of age group. Married women constituted 21 (77%) cases. The 14 (52%) belonged to rural area while 13 (48%) belonged to urban area. The chemist was found to be source of procurement in 19 (70%) cases, private practitioner in 6 (22%) cases and only two consumed pills after consultation with registered doctor. Conclusions: This study shows urgent need for legislation and restriction of drugs used for medical termination of pregnancy. Drugs should be made available via health care facilities under supervision to reduce maternal mortality and morbidity due to indiscriminate use of these pills.